School-based Support Teams as Communities of Enquiry: A Case of Developing Inclusive Practices in the Free State Province of South Africa - Makoelle, Tsediso (International Journal of Educational Sciences, 2014)
School-Based Support Teams were established by the South African National Department of Education in schools to deal with inclusive education and its implementation at school level. The role of these teams include, among others, organising support and establishing the individualised education programmes for vulnerable and learners perceived to be having barriers to learning.
Keywords: reflection.; inclusion; case study; collaboration; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education